Autoria no processo de (re) leitura e produção audiovisual da obra A hora da estrela por alunos do ensino médio - Martins, Daiana Orben (2017)
This work aims to understand how the gestures of authorship in the audiovisual re - reading of Clarice Lispector 's "The Hour of the Star", performed by students of the second year of high school in a private school in the city of Braço do Norte, SC. The methodological course of this research is constituted from Discourse Analysis, according to this theory, there is a necessary relation among the object, the techniques, the methodology and the theory on which the analysis is based. Based on Possenti (2009) and also Orlandi (2000, 2001, 2006), this study will also give attention to the relationship among the media, the school and the literature, making an intersection with the reading of authors such as Citelli (2000, 2001), Orofino (2005), Lajolo (1994), Zilbermann (2008) and documents such as PCN (2006). The main objective of the study is to understand the students ‘gestures of interpretation, production and authorship into the realization of the audiovisual version of Clarice Lispector´s work. As Possenti (2009) states, the concept of authorship has more to do with the concepts of speaker and singularity, in other words, for the author a good text can only be evaluated into the discursive terms, while the quality of the text goes through the question of subjectivity and its inclusion in a historical framework. We also work with the concept of Image Text, formulated by Tania Conceição Clemente de Souza (2001). For this researcher, the image means, it does not speak, and therefore it must be analyzed into the full dimension of its characteristics. Elements such as color, angle, trace, light and shadow are fundamental and constituent components for both analyzing and interpreting an image. Throughout the course by the activity proposed, students had not only to rework statements, but also to manage and reconcile voices of various authors. According to Orlandi (2006) being an author means to historicize one´s saying, therefore, we can affirm, that the students have placed themselves into the author position not only of the verbal text, but also we have found indications of authorship in the Text of Image. Since they have been able to redefine the audiovisual version created from the source text, generating new interpretive movements.